Mechanisms of miR-29a-5p involvement in osteogenic phenotype transformation and cellular regulation of vascular smooth muscle and thus influencing calcification in VSMCs in chronic kidney disease: miR-29a-5p effects on vascular smooth muscle - Deng, Hui; Xu, Honglan; Luo, Yuxuan (Cellular and Molecular Biology, 2022)
Vascular calcification is one of the major complications of chronic kidney disease (CKD), which could be further accelerated by the osteogenic transition and apoptosis of smooth muscle cells, thereby advancing the progression of renal diseases and increasing the mortality rate of cardiovascular events. MicroRNA is a kind of key regulator in the phenotypic transition of vascular smooth muscle cells (VSMCs), but its role remains unclear in VSMCs. In this study, VSMCs were stimulated by platelet-derived growth factors – BB (PDGF-BB) in varying concentrations to establish the VSMC dysfunction models. The relative expression of miR-29a-5p was quantified via the quantitative real-time polymerase chain reaction (qRT-PCR). The proliferation of VSMCs was determined via the BrdU method, analysis of cell cycle via flow cytometry, and the migration of VSMCs via Transwell assay. Expression of γ-secretase activating protein (GSAP) and markers of VSMC differentiation, including α-SMA, SM-22α, SMMHC and Calponin, was quantified via the Western blot. The targeting relationship between the 3’-UTR of miR-29a-5p and GSAP was validated through the dual-luciferase reporter gene assay. As a result, we found that PDGF-BB could trigger a decrease of miR-29a-5p in a time- and dose-dependent manner (P < 0.05). Overexpression of miR-29a-5p could curb the effect of PDGF-BB on the proliferation and migration of VSMCs while upregulating the expression of markers of differentiation (P < 0.05). In addition, the expression of GSAP was also affected by the negative regulation of miR-29a-5p, while the restoration of GSAP eliminated the effect of miR-29a-5p on the VSMCs partially (P < 0.05). Moreover, vascular calcification models were also established in the CKD rats, suggesting that the inhibition of GSAP could prevent PTH-induced vascular calcification in CKD rats. In conclusion, miR-29a-5p could inhibit the PDGF-BB-induced proliferation, migration and phenotypic transition of VSMCs via targeting GSAP. Thus, miR-29a-5p/GSAP might be a potential target for the treatment of vascular calcification.